PENGARUH PEMBELAJARAN PENDIDIKAN AGAMA ISLAM TERHADAP MORAL CREDENTIAL EFFECT MAHASISWA UNIVERSITAS MATH'LAUL ANWAR BANTEN TERHADAP TRADISI TAHLILAN - Humaeroh, Eneng (LPPM Institut Nida El-Adabi, 2023)
The moral credential effect has a huge clout to change other people's sight. The community are ethnicity that potentially has views that change from time to time, including tahlilan tradition that is commonly done by the Muslim community. In community interaction, every person is given influence to each other or has a tendency to follow moral action. This research wants to analyse social phenomena which happened and the alteration that occurred in it. Using instrument observation and research interview resulted from tahlil tradition’s view changed and became a moral view that is more acceptable and make sense, this thing constitutes inclination to another opposite group. Respondents consisted of undergraduate students from the Islamic Religious Education study program at Math'laul Anwar University, Banten, who took part in Islamic Religious Education (PAI) lessons and discussions related to the tahlilan tradition. This research yield shown there’s a fundamental change related tahlil tradition in the community in which students exist. Concept change and this view show the occurrence of moral belief securities. This social phenomenon is very interesting if in-depth research.